Speed Control of DC Motor Using Single Phase Matrix Converter - Boydak, Merve; Orhan, Ahmet; Caliskan, Abuzer (Ieee, 2020)
This paper focuses on speed control of DC motor using new driver circuit of Single-Phase Matrix Converter (SPMC). Changing of modulation index has been provided with closed loop PI control. Thus, the voltage applied to the armature has been controlled and rotating of motor at the desired speed has been enabled. Insulated Gate Bipolar Transistors (IGBTs) are used to perform SPMC topology. Sinusoidal Pulse Width Modulation (SPWM) technique is used to obtain switching signals. MAT LAB / Simulink is used to implement simulation.
IEEE 2nd Global Power, Energy and Communication Conference (GPECOM) -- OCT 20-23, 2020 -- ELECTR NETWORK
Keywords: DC motor; single phase matrix converter with reduced switch count; AC-DC converter; sinusoidal pulse width modulation (SPWM)